A framework to estimate the willingness to pay of household for airquality improvement: a case study in Klang Valley, Malaysia - Sarabdeen, Masahina; Rafia, Afroz; Duasa, Jarita; Mohamad, Noorihsan (Ontario International Development Agency, 2012)

(untitled)
The main objective of this study is to estimate the willingness to pay (WTP) of the household for improving the air quality in Klang Valley, Malaysia as a result of implementation of two types of transport hypothetical policy options. Survey method will be conducted to estimate how much the household in Klang Valley would value lowering the health risks associated with poor air quality. The popular method, contingent valuation method (CVM) has been used to estimate WTP for avoiding the ill health episodes due to air pollution or to improve the air quality in Klang Valley. The survey results will be analyzed using Binary Logit Model. This study is expected to minimize the problem of mismatch in terms of services that can be supplied by government and what the public really wants and is willing to pay for.